1990
DOI: 10.1007/bf02442351
|View full text |Cite
|
Sign up to set email alerts
|

Effect of estrogens on prolactin secretion in transsexual subjects

Abstract: The effect of estrogens on the secretion of prolactin in 8 different groups of transsexual subjects was studied. Two different types of estrogens, estradiol or its conjugate and ethinyl estradiol, were used. Different doses and durations of exposure were employed. Plasma levels of prolactin and SHBG after estrogen exposure were compared with corresponding levels before treatment. Results showed that for estrogens to exert an enhancing effect on the secretion of prolactin, three factors needed to be considered:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
3
1
Order By: Relevance
“…Bosinski et al. reported that only 18.3% of subjects had regular cycles (although the sample size was small with only 18 patients) [13], Pache and Fauser reported that 76% had regular cycles [18] compared to 91% in our study, while Goh and Ratnam[19] reported 100% in 20 FTM transsexuals. Bosinski et al.…”
Section: Discussioncontrasting
confidence: 50%
“…Bosinski et al. reported that only 18.3% of subjects had regular cycles (although the sample size was small with only 18 patients) [13], Pache and Fauser reported that 76% had regular cycles [18] compared to 91% in our study, while Goh and Ratnam[19] reported 100% in 20 FTM transsexuals. Bosinski et al.…”
Section: Discussioncontrasting
confidence: 50%
“…Given the high frequency of occult prolactinoma formation (Molitch, 1997) and the apparent rarity of prolactinoma in genetic males during cross‐sex hormone therapy, a direct link between exogenous oestrogens and prolactinoma induction in humans cannot be drawn. Contrary to early conclusions (Asscheman et al ., 1988; Goh & Ratnam, 1990), safety data about adverse pituitary effects of oestrogens in genetic males are reassuring.…”
Section: Specific Effects Of Cross‐sex Hormone Treatmentmentioning
confidence: 99%
“…Several studies have reported increasing prolactin levels in MtFs during CHT (Asscheman et al., ; Goh & Ratnam, ; Gooren, Harmsen‐Louman, & van Kessel, ; Wierckx et al., ). In addition, 13 cases of prolactinomas have been described in MtFs during CHT (Asscheman et al., ; Bunck et al., ; Cunha et al., ; García‐Malpartida, Martín‐Gorgojo, Rocha, Gómez‐Balaguer, & Hernández‐Mijares, ; Gooren, Assies, Asscheman, de Slegte, & van Kessel, ; Kovacs, Stefaneanu, Ezzat, & Smyth, ; Serri, Noiseux, Robert, & Hardy, ).…”
Section: Introductionmentioning
confidence: 99%
“…After SRS, in MtFs, anti‐androgens are ceased while other hormonal medication will be continued mostly in the same doses (Coleman et al., ). Although CHT is generally considered to be safe, it may affect various organ systems including the prolactin‐producing pituitary gland (Asscheman, Gooren, Assies, Smits, & de Slegte, ; Goh & Ratnam, ).…”
Section: Introductionmentioning
confidence: 99%